2008
DOI: 10.1177/1086026608321327
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Inequality in Metropolitan America

Abstract: This study compares the environmental hazard burden experienced by Blacks, Hispanics, Pacific Islanders, Native Americans, Asian Americans, and Whites in each of the 329 metropolitan areas in the continental United States, using toxicity-weighted air pollutant concentration data drawn from the Environmental Protection Agency's Risk-Screening Environmental Indicators project to determine whether and to what degree environmental inequality exists in each of these metropolitan areas. After demonstrating that envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 50 publications
1
70
1
1
Order By: Relevance
“…These results are consistent with Morello-Frosch and Jesdale (2006), who showed that the segregation of a metropolitan area was associated with an increase in the health risk from air toxins for all racial groups. However, these results dispute more recent conclusions that suggest those metropolitan areas with higher levels of racial segregation of African-Americans are no more unequal in their exposure to air toxins than areas with lower segregation (Downey et al 2008).…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with Morello-Frosch and Jesdale (2006), who showed that the segregation of a metropolitan area was associated with an increase in the health risk from air toxins for all racial groups. However, these results dispute more recent conclusions that suggest those metropolitan areas with higher levels of racial segregation of African-Americans are no more unequal in their exposure to air toxins than areas with lower segregation (Downey et al 2008).…”
Section: Discussioncontrasting
confidence: 93%
“…This allows for investigation of whether there is an added risk of living in a block group with relatively more African-Americans, in a more segregated metro area, a question previously examined in this literature (Downey 2008). If the coefficient on this variable is positive, it would mean that if you compared two block groups with the same relative proportion of African-Americans, the one in a metro area with a higher segregation level will have a greater risk from air toxins.…”
Section: Model Specificationmentioning
confidence: 99%
See 3 more Smart Citations